1984
DOI: 10.1111/j.1471-4159.1984.tb00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Changes in Murine Trisomy 16: Delay in Cholinergic and Catecholaminergic Systems

Abstract: Two strains of Mus musculus musculus, C57BL/6J and CD-1, and Mus musculus poschiavinus, the tobacco mouse, were used to study the effects of increased gene dosage of mouse chromosome 16 (MMU 16). A developmental delay has been found in the brains of murine trisomy 16 (Ts16) fetuses. Both the brain weight (in all three strains) and DNA content (in CD-1) were reduced, while protein content was unchanged in Ts16 compared to normal littermates. The daily increments of weight and protein (except in M. m. poschiavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
(49 reference statements)
1
27
2
1
Order By: Relevance
“…The mice are born after 20 days of gestation, and the period from E l 3 to 18 roughly corresponds to human fetal brain development between 18 and 33 weeks. As in Down syndrome, the brain of Ts 16 mice has a lower than normal weight, reduced cortical thickness, and hypocellularity in regions such as the cerebellum, the basal forebrain (including cholinergic neurons), and the locus ceruleus (noradrenergic neurons) (Ozand et al, 1984;Singer et al, 1984;Kiss et al, 1989). Alterations begin to appear at early stages of brain development, during neuronal proliferation and migration.…”
Section: Morphological Studiesmentioning
confidence: 95%
“…The mice are born after 20 days of gestation, and the period from E l 3 to 18 roughly corresponds to human fetal brain development between 18 and 33 weeks. As in Down syndrome, the brain of Ts 16 mice has a lower than normal weight, reduced cortical thickness, and hypocellularity in regions such as the cerebellum, the basal forebrain (including cholinergic neurons), and the locus ceruleus (noradrenergic neurons) (Ozand et al, 1984;Singer et al, 1984;Kiss et al, 1989). Alterations begin to appear at early stages of brain development, during neuronal proliferation and migration.…”
Section: Morphological Studiesmentioning
confidence: 95%
“…On the other hand, MMU 16 contains 2-2.5 times more of the cellular genetic material [3,7]; although it is known that the more distal segment of the MMU 16 contains the syntenic loci [7] its mapping is far from complete. Shared symptomatology of DS and murine Tsl6 is indi cated by retarded growth of the central nervous system [9,15], congenital heart disease [3] and other malformations [15]. Additionally, increased SOD-1 activity (1.35 fold) [8] has been observed in Tsl6 embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuses, 14-17 days old, were removed into a sterile petri dish and examined for morphological charac teristics of trisomy 16 (i.e., anasarca, open eye lids, etc. [9], They were then placed in sterile tubes containing Eagle's minimal essential medium (MEM). Normal littermates were treated similarity (controls).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated significant reductions in the developmental accrual of ChAT, the presynaptic marker of cholinergic neurons, in the brains of fetal Ts16 mice, as compared to their euploid littermates (11,12). Histochemical studies of the BF have revealed a significantly reduced complement of acetylcholinesterase (AChE)-positive presumptive cholinergic neurons in Ts16 fetuses (13,14).…”
mentioning
confidence: 99%